Unveiling the Secrets: Reconstruction of Shredded Documents using Deep Learning - Paixão, Thiago M.; Boeres, Maria C. S.; Oliveira-Santos, Thiago (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2023: Anais Estendidos da XXXVI Conference on Graphics, Patterns and Images, 2023)
This work addresses the intricate task of reconstructing mechanically-shredded documents with potential application in forensic investigation. Our primary contributions consist of two novel deep learning approaches for fully automatic reconstruction tested on real-world shredded data that achieved state-of-the-art accuracy in more realistic scenarios. As a second major contribution, we introduce a novel framework for semi-automatic reconstruction inspired by the principles of active learning. The core of our proposal is a recommendation module that smartly flags potential errors in the reconstruction output (permutation of shreds) for human review, enabling even more enhanced reconstructions. The mentioned contributions and additional outcomes (datasets and experimental protocols) resulted in five relevant publications: three journal articles and two international conferences, including the premier IEEE / CVF Computer Vision and Pattern Recognition Conference (CVPR).